Beneath the pavement - Messham-Muir, Kit (2009)
Within the broader context of urban renewal in Newcastle NSW, this paper considers the importance of unauthorised tactical interventions in city placemaking in the form of laneway art, an ephemeral public art practiced in Australia’s urban centres. It takes the dichotomy of authoritative versus subversive space as the working framework and investigates the ways in which some emerging forms of public art radically reimagine the city. Particularly, this paper focuses on laneway art in Melbourne and Sydney. I will look at how laneway art creates a subversive space within the city, often existing in a ’carnivalesque’ relationship with official sanctioned culture. This paper also looks at how laneway art forms only part of a larger milieu that works across hard (physical) and soft (virtual) spaces, via the internet. As an urban cultural practice, this art suggests that the social and cultural transformation of a city can operate on a micro and tactical level, ways in which art in urban spaces can re-imagine the place of art and the art of place in the city. This paper argues that this emerging approach to public art can be understood as engaging in the city, its spaces and channels via a mode of practice similar to that suggested in Guy Debord’s idea of the ’derive’ - a tactically unpredictable ’drift’ across city spaces. Debord’s derive is a radical fragmentation of the nineteenth century Parisian flaneur, the uninvolved bourgeois stroller, made popular in archjtecture and urban planning through the work of twentieth-century thinker, Walter Benjamin. Unlike the flaneur’s stroll, the derive cuts across the arterial lines that ordinarily link the organs of the urban corpus. In this way, the derive reinscribes the city plan in unpredictable ways and opens it up to multiple, unstable and temporary reinterpretations. Laneway art, working often anonymously and illegally in the gaps and ’non-places’ of the city, breaks open the relatively stable and sanctioned meanings of urban spaces. Laneway art is often temporary, usually political and plays wittily with the psychogeography of urban spaces. This paper considers how this tactical reuse of urban public spaces contributes productively to the development of art and culture in the city.